Analisis Finansial Usaha Peternakan Itik Petelur dengan Sistem Pemeliharaan Intensif di Kecamatan Gadingrejo Kabupaten Pringsewu - Yuni Hidayah Sari; Teguh Endaryanto; Ktut Murniati (Politeknik Negeri Lampung, 2020)
This study aims to analyze the financial and sensitivity of the intensive system maintenance laying duck business in Gadingrejo Subdistrict of Pringsewu District. The location was chosen purposively in Gadingrejo Subdistrict, considering that the location is a duck center in Pringsewu. Data was collected in February 2019. Respondents were taken by census method with a total of 15 breeders. They were divided into six categories based on business experience, namely breeders with business experience of two years, four years, five years, six years, eight years and more than 10 years. The results showed that the laying duck business with intensive system maintenance in six categories was profitable and feasible to be developed based on investment criteria (Internal Rate Return (IRR), Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Gross Benefit Cost (Gross B/C), and Payback Period (PP)). The laying duck business was sensitive to decreas egg price and decreas production. Whereas the increase in production costs and the concentrate feed prices are only sensitive to the Payback Period investment criteria indicator. Keywords : duck breeder, financial, sensitivity